1979
DOI: 10.1159/000207620
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Activity and Bactericidal Function of PMN in Iron Deficiency

Abstract: In children with iron deficiency anemia, bactericidal capacity of polymorphonuclear leukocytes (PMN) and serum opsonic activity were studied. Nitroblue tetrazolium test (NBT), hexose monophosphate (HMP) shunt activation, and myeloperoxidase (MPO) activity of PMN of these cases were also examined. Bactericidal capacity and HMP shunt activation were found to be decreased in iron deficiency anemia (p > 0.001). MPO activity, NBT test, and serum opsonic activity were found to be within normal limits. After 11<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…In addition, defective neutrophil dicating selenium insufficiency in chronic iron deficiency bactericidal capacity due to iron deficiency may be exanemia accompanied by low GSH-Px activity in red cells plained to some extent by this interpretation [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, defective neutrophil dicating selenium insufficiency in chronic iron deficiency bactericidal capacity due to iron deficiency may be exanemia accompanied by low GSH-Px activity in red cells plained to some extent by this interpretation [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…It might also shed some light on the neutrophil bac tericidal defect observed in iron deficiency and/or sele nium deficiency [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil myeloperoxidase, an iron metalloenzyme that generates reactive bactericidal halides during PMN phagocytosis, is reduced in iron deficiency states Turgeon-O'Brien et al, 1985;Yetgin et al, 1979). Myeloperoxidase-mediated killing is a redundant system; however, iron is also required for the production by phagocytic cells of reactive microbicidal oxygen species via the Fenton reaction .…”
Section: Effects Of Iron Deficiency On Immune Functionmentioning
confidence: 99%
“…Sub jects with ACD suffered from infections [5], inflammatory [8] or neoplastic [2] diseases. The mean age was 48 ±10 years for the IDA …”
Section: Patient Selectionmentioning
confidence: 99%
“…There is also prevailing opinion that intracellular bacterial killing by PMNs is impaired in the iron-defi cient state [5][6][7], Although Arbeter et al [7] reported that a deficiency in MPO activity was responsible for the abnormal function of PMNs, Yetgin et al [8] found normal values for MPO in IDA. Thus, there is some controversy on the role of iron in bactericidal capacity of PMNs in IDA, while this aspect of im munocompétence is not well documented in ACD.…”
Section: Introductionmentioning
confidence: 99%